The first Acanthamoeba keratitis case in the Midwest region of Brazil: diagnosis, genotyping of the parasite and disease outcome - Alves,Daniella de Sousa Mendes Moreira (2018)
Abstract We report an Acanthamoeba keratitis case associated with the use of contact lens in a 28-year-old female from Brasília, Brazil. Samples from corneal scraping and contact lens case were used for culture establishment, PCR amplification, and partial sequencing (fragments of ~400kb) of small subunit rDNA; both culture and PCR were positive. The sequence analyses of the cornea and of isolates from the contact lens case showed similarity with the T4 genotype. To the best of our knowledge, this is the first report of T4 Acanthamoeba keratitis case from the Midwest region of Brazil.